Case Report: Collapsing Focal Segmental Glomerulosclerosis After Initiation of Ado-Trastuzumab Emtansine Therapy - Hakroush, Samy; Wulf, Svenja; Gallwas, Julia; Tampe, Björn (Frontiers in Oncology, 2021)
Ado-trastuzumab emtansine (T-DM1) is an antibody-drug conjugate consisting of the monoclonal antibody trastuzumab linked to the maytansinoid DM1 with potential antineoplastic activity, and approved for human epidermal growth factor receptor 2 (HER2)-positive breast cancer. An analysis of the US Food and Drug Administration (FDA) Adverse Event Reporting System identified 124/1243 (10%) renal adverse events for trastuzumab. However, there are no published case reports describing kidney biopsy findings related to nephrotoxicity of either trastuzumab or T-DM1. We report kidney biopsy findings in a case of nephrotic range proteinuria due to collapsing FSGS and tubular injury after initiation of T-DM1 therapy. After systematic exclusion of other causes, it is likely that the observed collapsing FSGS was associated with the prior initiation of T-DM1 therapy. This is further supported by the clinical course with improvement of proteinuria and kidney function three weeks after discontinuation of T-DM1 therapy without further specific treatment. In summary, we provide the first report of kidney biopsy findings in a case of nephrotic range proteinuria after initiation of T-DM1 therapy due to collapsing FSGS. This issue is especially relevant since T-DM1 is widely used and nephrologists have to be aware of this potentially rare, but severe complication.